Zimbabwe : First and Second Reviews Under the Staff Monitored Program. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2014)
EXECUTIVE SUMMARY Zimbabwe's performance under the Staff-Monitored Program (SMP) has been broadly satisfactorily through the difficult electoral transition period, and the authorities have taken corrective measures to restore a track record of policy implementation going forward. In the attached Letter of Intent (LOI), the authorities outline progress in implementing the SMP; the agreed quantitative targets and structural benchmarks to be monitored for the third review; and their plans to advance the structural reform agenda and to more generally strengthen performance under the SMP. Performance under the staff-monitored program. The SMP provided a useful anchor for Zimbabwe in an election year. However, progress in implementing the program was slowed by a long electoral process and a protracted post-election transition, as well as an adverse external environment. Thus, a number of quantitative targets and structural benchmarks were not met. The authorities have began implementing policy measures and a program of reforms aimed at addressing the fiscal gap that has emerged for 2014; improving the quality of public expenditures; enhancing financial sector stability; and moving forward delayed structural reform measures. The authorities have reiterated their continued commitment to the policies agreed under the SMP, and to enhanced engagement with the creditors and the international community. The authorities have agreed to the publication of the Letter of Intent, and the staff report.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet